PENGARUH BIAYA PAKAN TERHADAP KEUNTUNGAN PETERNAK BABI DI DESA WERDHI AGUNG KECAMATAN DUMOGA BARAT - Matialo, Chrestian C; Elly, F H; Dalie, S; Rorimpandey, B (ZOOTEC, 2020)
THE EFFECT OF FEED COST ON THE PROFIT OF PIG FARMERS IN WERDHI AGUNG VILLAGE, WEST DUMOGA DISTRICT. This study aims to determine  influence of feed cost on pig farmer’s profits. This  research was conducted by survey method to 30 respondents of pig farmers in werdhi agung village, west dumoga subdistrict. The determination of samples was carried out by purposive sampling, with the consideration of breeders  have pig over 20 heads and more than one year experienced on pig farm. The analytical method used in this study was multiple linear regression analysis. Study results showed the cost of consentrate feed, bran, corn, had significantly effect on the profits of pig farmers simultaneously Partially the cost of concentrate had a very significant effect, while the cost of ingredient feed materials of bran, corn, had no significant effect on profits.